Unlocking sustainability: exploring the nexus of green banking, digital transformation, and financial performance with foreign ownership moderation - Indra Siswanti; Hosam Alden Riyadh; Yohanes Ferry Cahaya; Embun Prowanta; Baligh Ali Hasan Beshr (Discover Sustainability)
Abstract The purpose of this research is to empirically test and analyze the impact of green banking, digital transformation, and asset quality on the financial performance of commercial banks with foreign ownership as a moderator. Additionally, it aims to test and analyze the financial performance of sustainable business practices for commercial banks. This study was conducted on commercial banks, specifically focusing on bank groups categorized by core capital levels 3 and 4, listed on the Indonesia Stock Exchange, covering the period from 2017 to 2022. This research employed a judgment sampling technique, encompassing a total of 47 conventional commercial banks. Panel data regression analysis, a data analysis technique, used three variables: the dependent variable, the independent variable, and the moderation variable. The research unveiled that green banking does not appear to have a significant positive impact on financial performance, whereas digital transformation shows a clear positive effect. Non-performing loans, a measure of asset quality, also affect financial performance. Additionally, foreign ownership strengthens the impact of green banking on the financial performance of commercial banks in Indonesia. However, foreign ownership does not enhance the effect of digital transformation. Finally, foreign ownership plays a moderating role in the relationship between asset quality and financial performance in these banks. Ultimately, financial performance has a significant positive influence on sustainable business, suggesting that stronger financial performance contributes to the long-term sustainability of a bank’s operations. The implications of these findings are, first and foremost, that financial institutions should prioritize incorporating sustainable and environmentally friendly practices into their operations to improve their overall financial performance and emphasize the critical role of digital transformation in enhancing financial performance. Consequently, financial institutions are required to allocate resources towards information technology infrastructure and cultivate digital capabilities to adapt to evolving customer demands, such as offering 24/7 banking services from any location. Secondly, financial institutions should not stay far away from digital disruption, but rather embrace it and adapt their strategies accordingly, which includes allocating an adequate budget for IT infrastructure investment and accessing digital services that meet the banking industry’s demands, resulting in effective communication of sustainable practices.